Surgical care in the public health agenda - Mário Scheffer; Saurabh Saluja; Nivaldo Alonso (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2017)
The current article examines surgical care as a public health issue and a challenge for health systems organization. When surgery fails to take place in timely fashion, treatable clinical conditions can evolve to disability and death. The Lancet Commission on Global Surgery defined indicators for monitoring sustainable universal access to surgical care. Applied to Brazil, the global indicators are satisfactory, but the supply of surgeries in the country is marked by regional and socioeconomic inequalities, as well as between the public and private healthcare sectors.